Solanum malmeanum, a promising wild relative for potato breeding - Nicolao, Rodrigo; Gaiero, Paola; Castro, Caroline M.; Heiden, Gustavo (Frontiers in Plant Science, 2023)
Crop wild relatives are gaining increasing attention. Their use in plant breeding is essential to broaden the genetic basis of crops as well as to meet industrial demands, for global food security and sustainable production. Solanum malmeanum (Solanum sect. Petota, Solanaceae) is a wild relative of potatoes (S. tuberosum) from Southern South America, occurring in Argentina, Brazil, Paraguay and Uruguay. This wild potato has been largely confounded or historically considered as conspecific with S. commersonii. Nevertheless, it was just recently reinstated at the species level. Due to the instability of the correct application of this species name and discordant species circumscriptions and morphological borders applied to recognize it, retrieving information on its traits and applied uses is challenging. To overcome these difficulties, we performed a thorough literature reference survey, herbaria specimens’ identification revision and genebank database queries to review and update the information available on this neglected potato wild relative towards increasing research on it to fully understand and explore its potential for potato breeding. Scarce studies were carried out concerning its reproductive biology, resistance against pests and diseases as well as tolerance to abiotic stresses and evaluation of quality traits. Furthermore, many discrepancies are found in previous reports that treat S. malmeanum under different scientific names. The scattered and scarce information available make it less represented in genebanks and genetic studies are missing. We compile, update and present available information for S. malmeanum on taxonomy, geographical distribution, ecology, reproductive biology, relationship with its closest relatives, biotic and abiotic stresses resistance traits, and discuss ways to overcome sexual barriers of hybridization and future perspective for its use in potato breeding. As a final remark, we highlight that this species potential uses for potato breeding have been neglected and must be unlocked. Thus, further studies on morphological and genetic variability with molecular tools are fundamental for an efficient conservation and applied use of this promising genetic resource.